Bubbles Templated Interconnected Porous Metallic Materials: Synthesis, Surface Modification, and their Electrocatalytic Applications for Water Splitting and Alcohols Oxidation. Issue 41 (3rd November 2022) - Arshad, Farhan; Tahir, Aleena; Haq, Tanveer Ul; Munir, Akhtar; Hussain, Irshad; Sher, Falak
Abstract: Porous metallic foams play a vital role in a diverse range of applications including electrocatalysis, electrochemical sensing, energy conversion and storage systems. Recently, template‐free electrochemical deposition or dynamic bubbles templating techniques have been very useful to precisely control the nanostructured metallic architecture without using any additional organic or inorganic template. Dynamic hydrogen/oxygen bubbles template electrodeposited metallic foams give micro/nano porosity with controlled pores size, pores channels and surface decorated nanoparticles. In this review, we describe the uniqueness of bubble‐templating electrochemical deposition techniques, their detailed implementation towards the synthesis of novel nanostructured metallic foam, and the progress made in the field of hydrogen bubbles, oxygen bubbles, and their derived templating approaches for the development of advanced nanometallic foam and their future prospective. Some modifications of porous metallic foams by galvanic replacement, chemical/electrochemical dealloying process, annealing and decoration of metallic and non‐metallic composites on the porous metallic foam are also summarized. Moreover, the role of porous metallic foam in electrochemical water splitting and alcohol oxidation reaction by offering a short diffusion pathway and concluding remarks about the recent development and future perspective of porous foam in the frontiers of surface structure are also critically reviewed. Abstract : This review focuses on the most recent advances in the field of nanostructured porous metallic foams (NMFs) fabricated using the dynamic hydrogen/oxygen bubbles templating approach, as well as the modification of these NMFs through different methods. The electrocatalytic applications of NMFs for water splitting and alcohols oxidation are also summarized.